2018
DOI: 10.1515/multi-2017-0077
|View full text |Cite
|
Sign up to set email alerts
|

“English as corporate language” in the multilingual reality of multinational companies

Abstract: This conceptual paper advances the notion of “English as corporate language” in the multilingual reality of multinational companies (MNC) with novel insights from the English as lingua franca (ELF) paradigm of sociolinguistics. Inspired by Goffman, Erving. 1959.The presentation of self in everyday life. New York: Doubleday. dramaturgical metaphor of social life, we develop the notion of English as corporate language by making a distinction between the frontstage official language used in corporate communicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…International management researchers could in particular make use of the concept of BELF – English as Business Lingua Franca – to study the different configurations of English in the MNC. An interesting question is, for example, whether there indeed are at least two different ‘Englishes’ – the ‘official’ corporate language resembling English as native language and the ‘everyday’ BELF (Kankaanranta et al, ). Furthermore, it is not clear to what extent both types of corporate language are shaped by the values and ideologies of the MNC or by the wider societal context in which the firm is embedded.…”
Section: Discussion: Consequences Of Underlying Assumptions For Futurmentioning
confidence: 99%
“…International management researchers could in particular make use of the concept of BELF – English as Business Lingua Franca – to study the different configurations of English in the MNC. An interesting question is, for example, whether there indeed are at least two different ‘Englishes’ – the ‘official’ corporate language resembling English as native language and the ‘everyday’ BELF (Kankaanranta et al, ). Furthermore, it is not clear to what extent both types of corporate language are shaped by the values and ideologies of the MNC or by the wider societal context in which the firm is embedded.…”
Section: Discussion: Consequences Of Underlying Assumptions For Futurmentioning
confidence: 99%
“…Based on the findings here, BELF as a complex communication resource is an important component of corporate language, but so are the local 'company speak' and sometimes a more formal, NS-based English. Kankaanranta et al (2018b) claim that 'English as corporate language' can indeed encompass both NS-like linguistic proficiency and the more fluid BELF resource, however, they indicated that for most employees the latter would suffice. While this might be true to a certain extent, extensive English use was in the present study seen to permeate all levels of the MNCs, and advanced skills in the corporate language still appeared to have some gatekeeping function (Piekkari et al 2014).…”
Section: Resultsmentioning
confidence: 96%
“…The article thus reports on the individual experiences of nine Norwegian business professionals working in six different MNCs, which limits any claims respecting generalizability. However, BELF use is always emergent and varies across contexts (Kankaanranta et al 2018b), and there- fore theory development in this field will be in constant flux. Further, Eisenhardt/Graebner (2007) claim that multiple case studies are excellent for further development of emergent theories, as knowledge can be found inductively, and patterns may appear across cases.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations